The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/pr.2017.148
|View full text |Cite
|
Sign up to set email alerts
|

Kidneys in 5-year-old preterm-born children: a longitudinal cohort monitoring of renal function

Abstract: BackgroundBeing aware of the impact of low birth weight on late-onset hypertension, our aim was to describe systolic blood pressure (sBP) and renal function in 3-5-year-old preterm-born children and to determine which perinatal factors or childhood factors were associated with an altered renal function at 5 years in these children.MethodsThis was a prospective longitudinal cohort study of children born at 27-31 weeks of gestation and included at birth and examined at 3, 4, and 5 years of age. The primary outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
3
4
Order By: Relevance
“…The overall prevalence of hypertension in this cohort was higher than that of the previous reports of hypertension in children born preterm and VLBW, ranging from 6-13% 5,6,22 . This discordant nding could be explained by the fact that the present study used ABPM that can detect masked hypertension, while the previous studies used only the o ce blood pressure measurements.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…The overall prevalence of hypertension in this cohort was higher than that of the previous reports of hypertension in children born preterm and VLBW, ranging from 6-13% 5,6,22 . This discordant nding could be explained by the fact that the present study used ABPM that can detect masked hypertension, while the previous studies used only the o ce blood pressure measurements.…”
Section: Discussioncontrasting
confidence: 82%
“…The other studies also reported maternal preeclampsia and antenatal steroid as the additional risk factors for hypertension. 5,6 However, this study showed no association between these factors and hypertension. This might be the result of a small number of participants in the present study.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…These PWV values were considered abnormal without defined reference values; we therefore think that validating the pOpmètre1 in large cohorts of very young children could allow routine PWV measurement. Indeed, during consultation with the specialist pediatrician, a longterm screening and follow-up could be realized in perinatology networks, pediatric nephrology, and pediatric cardiology for an optimal cardiovascular prevention in children [35][36][37][38][39].…”
Section: Plos Onementioning
confidence: 99%
“…In preterm survivors, there is a high rate of longterm complications such as recurrent hospitalizations, long-term neurodevelopmental impairment, and chronic health problems, including hypertension and vascular change. Previous studies have shown that preterm with low birth weight is a risk factor for higher office blood pressure compared with that of the term and normal birth weight controls [3][4][5][6].…”
Section: Introductionmentioning
confidence: 97%